PERAN GURU KELAS DALAM MENANGANI PERILAKU BULLIYING SISWA KELAS II DI SD NEGERI BUNGKUS - Novanezha Diamondica; Aprilia Noor Widyaningrum; Agustin Setia Bekti; Helen Risma Fatmawati; Novi Khoiriyati; Danuri (LPPM Universitas Widya Dharma, 2024)
This research aims to examine the role of class teachers in dealing with bullying behavior in class II students at SD Negeri Bungkus. The research method used is qualitative research with a descriptive approach. The research results show that class teachers not only act as educators, but also as social facilitators and guides for students in creating a safe and conducive learning environment in dealing with bullying through various strategies, such as prevention, socialization, and collaboration with various related parties. The class teacher was identified as the main agent in creating a safe and conducive learning environment in class II of SD Negeri Bungkus. In conclusion, the active participation of classroom teachers in implementing prevention and intervention strategies can effectively reduce cases of bullying in the school, as well as improve the overall well-being of students. Thus, broader and in-depth research in this area can provide more comprehensive insight into the role of classroom teachers in dealing with bullying, as well as produce more effective strategies for creating safe and inclusive learning environments for all students.